(untitled) (Research, Society and Development, 2021)
Objective: to prepare a checklist for the screening of hearing and speech disorders of elderly people by non-speech-language pathologists. Methods: methodological research of a quantitative approach, carried out from December 2018 to January 2019, initially with a group of experts for the 1st version of the checklist and later with a group of non-speech therapists for the 2nd version of the checklist, by means of a previously elaborated evaluation instrument. The analysis was performed through the content validation index grater than or equal to 0.78. Results: the first version of the checklist was evaluated by 10 participants of the expert group, originating the 2nd version evaluated by 30 participants of the group of non-speech therapists, categorized and allocated on digital spreadsheet and variables analyzed descriptively. The content validation index was considered greater than or equal to 0.78, using the Likert scale as the scoring method, ending with the 3rd version of the checklist. Conclusion: the checklist was created and validated in this initial step. It is an easy language tool and simple application. Go to the other validation steps.